(untitled) (Medicine Today, 2024)
Introduction: Close proximity of urinary tract and genital systems in females poses potential risk of fistulas formation during surgical interventions. Gynaecological malignancy, bleeding, prolonged surgery, the presence of active infection during operation, endometriosis, large uterus, previous pelvic operation, pelvic adhesions and myoma uteri are major predisposing factors that may increase the risk of urological injuries & genitourinary fistulas. Genitourinary fistulas result in continuous or intermittent urinary incontinence and a significant public health issue with negative physical, emotional and social impacts on individuals. Materials and Methods: This cross sectional observational study was conducted in Department of Obstetrics &Gynaecology, Bangabandhu Sheikh Mujib Medical University, Dhaka, from 27th March 2017 to 26th September 2017. The sample was collected by purposive sampling technique. The study subjects were women with iatrogenic fistula (diagnosed after a clinical examination and investigations) attended in out-patients or in-patients department. Result: Mean age of patients was 32.5 ± 9.54 years. Vesicovaginal fistula was commonest cause for iatrogenic genitourinary fistula, present in 34 patients. Ureterovaginal fistula was 10 patients and 6 patients detected urethrovaginal. Aetiological factors revealed that, 46.0% occurred during vaginal hysterectomy, 18.0% due to abdominal hysterectomy, 20.0% due to laparotomy with salphingoophorectmy and 16.0% during laparotomy with cystectomy. Conclusion: The commonest urogenital fistula is the vesicovaginal fistula. Urinary leakage following gynaecological surgery is a dreaded complication due to the formation of urogenital fistula. Thorough evaluation, using all diagnostic tools for complete diagnosis, understanding the pathophysiology and choosing the best surgical procedure are mandatory to obtain good outcomes after the surgical procedures. Medicine Today 2024, Vol.36 (2): 110-113